Respuesta :
Answer:
6-3c-C
Step-by-step explanation:
3(2-c)-C
3(2)-3(c)-C
6-3c-C
Answer:
[tex]\Large\boxed{6-4c}[/tex]
Step-by-step explanation:
GIVEN:
[tex]\Large\boxed{\textnormal{SUBJECT: MATH}}[/tex]
3(2 - c) - C
To solve this problem, first you have to isolate by the c from one side of the equation.
SOLUTIONS:
First, you have to use distributive property.
[tex]\Large\boxed{\textnormal{DISTRIBUTIVE PROPERTY}}[/tex]
[tex]\displaystyle A(B+C)=AB+AC[/tex]
A=3
B=2
C=C
Rewrite the whole problem down.
[tex]\displaystyle 3*2-3c[/tex]
Multiply.
[tex]\displaystyle 2*3=6[/tex]
[tex]\displaystyle 6-3c[/tex]
[tex]\displaystyle 6-3c-c[/tex]
Solve.
Add or subtract the elements to from left to right.
[tex]\displaystyle -3c-c=\boxed{-4c}[/tex]
[tex]\Large\boxed{6-4c}[/tex]
Therefore, the correct answer is 6-4c.